Should We Reconsider Lung Transplantation Through Uncontrolled Donation After Circulatory Death?. Issue 4 (6th February 2014) - Suzuki, Y.; Tiwari, J. L.; Lee, J.; Diamond, J. M.; Blumenthal, N. P.; Carney, K.; Borders, C.; Strain, J.; Alburger, G. W.; Jackson, D.; Timar, J.; Berg, J.; et al.
<x xml:space="preserve">Abstract</x> Lung transplantation through controlled donation after circulatory death (cDCD) has slowly gained universal acceptance with reports of equivalent outcomes to those through donation after brain death. In contrast, uncontrolled DCD (uDCD) lung use is controversial and requires ethical, legal and medical complexities to be addressed in a limited time. Consequently, uDCD lung use has not previously been reported in the United States. Despite these potential barriers, we present a case of a patient with multiple gunshot wounds to the head and the body who was unsuccessfully resuscitated and ultimately became an uDCD donor. A cytomegalovirus positive recipient who had previously consented for CDC high‐risk, DCD and participation in the NOVEL trial was transplanted from this uDCD donor, following 3 h of ex vivo lung perfusion. The postoperative course was uneventful, and the recipient was discharged home on day 9. While this case represents a "best‐case scenario, " it illustrates a method for potential expansion of the lung allograft pool through uDCD after unsuccessful resuscitation in hospitalized patients.